Effects of Stress Management Training on Cognitive Avoidance and Emotion Regulation Strategies in Female Students with Social Anxiety Disorder: A Mindfulness and Emotional Schema Therapy Approach - Samaneh Hayatipoor; Sasan Bavi; Ali Khalafi; Zahra Dasht Bozorgi; Abdolamir Gatezadeh (Shiraz University of Medical Sciences, 2024)
Background: Students with a social anxiety disorder (SAD) face a variety of problems such as early dropout, academic failure, and avoidance of social situations. The present study aimed to investigate the effects of mindfulness-based stress reduction training on cognitive avoidance and emotion regulation strategies in female students with SAD through an emotional schema therapy (EST) approach.Methods: In this semi-experimental study, a Pretest-Posttest Control Group design was used. The study population included female high school students with SAD in Ahvaz, Iran, in 2023. Out of 120 students with SAD who met the inclusion criteria, 75 were randomly selected as the study participants and were then assigned to three groups of 25 (two experimental groups and one control group). Training sessions for mindfulness-based stress management and EST were conducted in eight 90-minute sessions twice a week. For data collection, the Cognitive Avoidance Questionnaire and Emotion Regulation Questionnaire were used. Data analysis was done using the ANCOVA test and SPSS version 23. P-value less than 0.05 was considered significant.Results: In the posttest, mean±SD for cognitive avoidance, reappraisal, and suppression in the mindfulness-based stress reduction training group was 50.71±6.78, 32.87±2.65, and 14.08±5.68, respectively; suggesting a significant difference as compared with the control group (82.91±2.18, 12.53±6.75, and 20.81±2.74) (P<0.001). In addition, mean±SD for cognitive avoidance, reappraisal, and suppression in the EST group and the post-test phase was 61.52±5.71, 38.91±1.15, and 10.36±7.32, respectively; suggesting a significant difference as compared with the control group. The mindfulness-based stress management training was more effective than EST in reducing cognitive avoidance (P<0.001). By contrast, EST was more effective than mindfulness-based training in improving emotion regulation strategies (P<0.001).Conclusion: The study results suggested that mindfulness-based stress management training and EST can effectively reduce cognitive avoidance and improve emotion regulation strategies in students with SAD.